If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 18 + -6x + 38 = 0 Reorder the terms: 18 + 38 + 4x + -6x = 0 Combine like terms: 18 + 38 = 56 56 + 4x + -6x = 0 Combine like terms: 4x + -6x = -2x 56 + -2x = 0 Solving 56 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -2x = 0 + -56 Combine like terms: 56 + -56 = 0 0 + -2x = 0 + -56 -2x = 0 + -56 Combine like terms: 0 + -56 = -56 -2x = -56 Divide each side by '-2'. x = 28 Simplifying x = 28
| 0=2t^2-13t+21 | | k+5=4k-10 | | -2x+4=-14 | | (5x^2-7x+7)*(6x+9)=0 | | Y+5=4y-10 | | 7+2s-6=6s+8-3s | | 9x^2-34x-8=0 | | 13t-48=2+14t | | 5-2x=-5 | | 3z+15=27 | | 16x^2-320=88x | | 4x-8=12+3x | | 4x^2-2x-9=7x+8 | | 2(4x-3)-=4+2x | | 3z+17=27 | | 8a=3a+35 | | 6y-7=-2y+13 | | x(x+2)=168 | | 4x^2+47x+78=0 | | 15=b-5 | | 3+5n=16 | | -4+3x=-4 | | .3x=140+x | | .8333v+1.5=.875v+1.666 | | 2x^2+6x+9=225 | | (-4)=2x+5 | | 15=b-9 | | -6x-4=-10 | | 4(7x+8)+2=28x+34 | | 7x-2=2x+18 | | x+(x+1)+(x+2)=42 | | 5x+x+10=2*5x |